RESPON BERBAGAI VARIETAS JAMUR TIRAM TERHADAP MEDIA TANAM AMPAS TAHU DAN TEPUNG JAGUNG : Tofu Dregs, Oyster Mushrooms, Planting Media, Corn Flour, Varieties - Fitrianingsih, Dewi; Lunnadiyah Aprilia , Rennanti (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
This research aims to (1) determine the response of various oyster mushroom varieties to the planting medium of tofu dregs and corn flour, (2) determine the best planting medium for the response of each variety. The method used was Completely Randomized Design (CRD). Using factorial experiments. The factors tried were planting media and oyster mushroom varieties. The experimental data were analyzed using the F test, followed by the DMRT test at 5% level. The results of the research show that the best planting medium based on the initial growth of pinhead oyster mushrooms is a combination of nutrients from tofu dregs and corn flour in the pink oyster mushroom variety. Corn flour planting media provides the best results based on the long growth of mushroom stalks in the brown oyster mushroom variety. The tofu dregs planting medium provided the best results based on the results of the wet weight and dry weight of oyster mushrooms in the white oyster mushroom variety. The pink oyster mushroom variety produced the best results based on the initial appearance of pinheads in the growing medium combined with tofu dregs and corn flour. The brown oyster mushroom variety responded best based on the growth of stalk length in the corn flour growing medium. The white oyster mushroom variety responded best based on the results of wet weight and dry weight on tofu dregs growing media. The gray oyster mushroom variety responded best based on the wet weight results in corn flour growing media.